The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1111/dmcn.12613
|View full text |Cite
|
Sign up to set email alerts
|

Social cognition in children with epilepsy in mainstream education

Abstract: AimTo establish whether deficits in social cognition are present in children with generalized or focal epilepsy in mainstream education, and whether any relation exists between social cognition, communication, and behaviour measures.MethodIn a cross-sectional study, children with an epilepsy-only diagnoses in mainstream education (n=20 with generalized epilepsy; eight males, 12 females; mean age 11y 6mo, SD 2y 6mo; and n=27 with focal epilepsy; 12 males, 15 females; mean age 11y 8mo, SD 2y 2mo) and comparison … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
59
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 26 publications
(87 reference statements)
2
59
2
1
Order By: Relevance
“…These studies have provided evidence of specific impairments in particular epilepsy types, often with all groups showing poorer performance when compared with unaffected controls. We have recently found, in a small group of CWE, that ToM skills did not differ between generalized and focal seizure types and that no reliable relationships between task performance, communication, and behavior could be established [19]. Cognitive, psychiatric, and social adjustment problems are neurobehavioral comorbidities in CWE with normal intelligence, irrespective of syndrome [20,21].…”
Section: Introductionmentioning
confidence: 92%
“…These studies have provided evidence of specific impairments in particular epilepsy types, often with all groups showing poorer performance when compared with unaffected controls. We have recently found, in a small group of CWE, that ToM skills did not differ between generalized and focal seizure types and that no reliable relationships between task performance, communication, and behavior could be established [19]. Cognitive, psychiatric, and social adjustment problems are neurobehavioral comorbidities in CWE with normal intelligence, irrespective of syndrome [20,21].…”
Section: Introductionmentioning
confidence: 92%
“…For example, nearly all patients with autism have impairment in social skills. Several studies have revealed specific deficits in social cognition in patients with various forms of epilepsy [51][52][53].…”
Section: Epileptiform Discharges In Autismmentioning
confidence: 99%
“…Adults with frontal lobe epilepsy have diminished ability to understand other's thoughts, humor, emotions, and eye gaze expressions [17]; adults with temporal lobe epilepsy also have diminished ability to understand other's thoughts and beliefs [18]. Children and adolescents with epilepsy are at risk of deficit in social cognition by having less ability to recognize facial expressions and to understand thoughts and motivations of others [19,20]. Unfortunately, ToM studies in children with epilepsy are very limited.…”
mentioning
confidence: 99%
“…Previous studies have found associations between social competence and epilepsy type [22], early onset of epilepsy [22], epilepsy etiology [25], seizure types [25], and seizure frequency [26], as well as antiepileptic treatment [26]. Behavioral problems are more associated with early onset of epilepsy [19], generalized epilepsy type, and seizure frequency [27]. Early onset refractory temporal lobe epilepsy can compromise the development of recognizing facial expressions in children and adolescents and is associated with comprehension of affects and intentions.…”
mentioning
confidence: 99%